The use of dissolved oxygen-controlled, fed-batch aerobic cultivation for recombinant protein subunit vaccine manufacturing. Issue 48 (27th November 2015) - Farrell, Patrick; Sun, Jacob; Champagne, Paul-Philippe; Lau, Heron; Gao, Meg; Sun, Hong; Zeiser, Arno; D'Amore, Tony
Highlights: Some fed-batch bacterial cultivation approaches to recombinant protein production cannot maintain dissolved oxygen (DO) at acceptable levels. DO-stat fed-batch control can maintain DO-levels throughout the cultivation period at a scale up to 200 L. DO-stat supports growth for an extended period without loss of DO control. Higher recombinant protein titers are possible using DO-stat. A pre-determined feeding profile for larger-scale manufacturing can be leveraged from historical, small-scale DO-stat data. Abstract: A simple "off-the-shelf" fed-batch approach to aerobic bacterial cultivation for recombinant protein subunit vaccine manufacturing is presented. In this approach, changes in the dissolved oxygen levels are used to adjust the nutrient feed rate (DO-stat), so that the desired dissolved oxygen level is maintained throughout cultivation. This enables high Escherichia coli cell densities and recombinant protein titers. When coupled to a k L a -matched scale-down model, process performance is shown to be consistent at the 2 L, 20 L, and 200 L scales for two recombinant E. coli strains expressing different protein subunit vaccine candidates. Additionally, by mining historical DO-stat nutrient feeding data, a method to transition from DO-stat to a pre-determined feeding profile suitable for larger manufacturing scales without using feedback control is demonstrated at the 2 L, 20 L, and 200 L scales.